The business of creativity : how to build the right team for success - Granet, Keith, 1956- (2017)
"Long known as the go-to management consultant of the design world, Keith Granet reveals more of his clear-eyed insights about running a creative business in this follow-up to his book The Business of Design. While aimed at creative enterprises, Granet's advice, quickly summarized as "know what you do best and focus on that," applies to any organization, small or large, commercial or nonprofit. He delves into the skill sets and people needed to grow a business, as well as the things you don't need (bad clients, bad employees, negative energy), in an engaging and easy-to-implement manner. His shrewd understanding, gleaned from decades of consulting for brands like Harrods, Pantone, John Varvatos, and Urban Archeology, makes this essential reading for anyone managing a business or thinking of starting one"--
Keywords: Creative ability in business; Business planning; DESIGN / Reference; BUSINESS & ECONOMICS / General